1955
DOI: 10.1039/tf9555100071
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of electrochemical kinetics at constant overvoltage. The behaviour of the lead dioxide electrode. Part 5.—The formation of lead sulphate and the phase change to lead dioxide

Abstract: THE FORMATION OF THE SULPHATE LAYER Three different types of sulphate deposit were formed on the lead electrodes by polarizing them at -1.902, -1.884 and -1.864V with respect to the reversible lead dioxide potential in 2 N sulphuric acid at 25" C . The current time relationships obtained 93 9 , -1.864V ,, 0.253 V.(f) sulphate formed at -1.884 V oxidized at 0.368 V in 0.02 N sulphuric acid and 0.99 M sodium sulphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(79 citation statements)
references
References 2 publications
(3 reference statements)
8
71
0
Order By: Relevance
“…A possible explanation is that the pit bottom is controlled by a slow formation and growth of a non-continuous salt film that does not have the same properties than the continuous salt film present before the dissolution. In that scenario, the slowest process can be either the rate of growth of anodic crystals forming the non-continuous salt film [47] or the increase of pore length constituting the non-continuous salt film [48]. When the continuous salt film is formed, the current returns to the value measured before the dissolution (current 0 in Fig.…”
Section: Evidence Of Salt Film Presence At the Pit Bottommentioning
confidence: 99%
“…A possible explanation is that the pit bottom is controlled by a slow formation and growth of a non-continuous salt film that does not have the same properties than the continuous salt film present before the dissolution. In that scenario, the slowest process can be either the rate of growth of anodic crystals forming the non-continuous salt film [47] or the increase of pore length constituting the non-continuous salt film [48]. When the continuous salt film is formed, the current returns to the value measured before the dissolution (current 0 in Fig.…”
Section: Evidence Of Salt Film Presence At the Pit Bottommentioning
confidence: 99%
“…First, studies of electrochemical deposition of PbO 2 gained insight into the nucleation and growth process and its kinetics which enabled the development of the general theoretical nucleation and growth theory which could be applied not only to understand subtle details of PbO 2 electrodeposition but also for the electrocrystallization processes of other oxide layers as well as cathodically formed metal deposits. Indeed, experimental results and their analysis in the works of Fleishmann [1][2][3][4][5][6] and later by Abyaneh [7][8][9][10], and others [11][12][13][14][15][16] paved the way toward the development of the 2D/3D instantaneous and progressive nucleation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The principal nature of the transient is the falling current (I dl ), then a rising section (I max ) and again a falling section corresponding to double layer charging, nuclei appearance on the substrate and the subsequent growth of electroactive area as established nuclei grow. The earliest work on this "constant overvoltage" for studying the nucleation and growth of electrodeposited materials were done by researchers such as Pangarov and Rashkov [114] and Fleischmann and Thirsk [115]. The current-time transients they recorded showed maxima [115], followed by approximately exponential decay, which suggested that the nuclei were formed according to the equation…”
Section: Potentialmentioning
confidence: 99%
“…The earliest work on this "constant overvoltage" for studying the nucleation and growth of electrodeposited materials were done by researchers such as Pangarov and Rashkov [114] and Fleischmann and Thirsk [115]. The current-time transients they recorded showed maxima [115], followed by approximately exponential decay, which suggested that the nuclei were formed according to the equation…”
Section: Potentialmentioning
confidence: 99%